PERAN HISBAH DALAM PENGUATAN KELUARGA MUSLIM - Imam Taufik Alkhotob (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2025)
The family institution is the cradle of moral virtue, the strength of faith, and sound understanding, serving as the foundation for improving the condition of a nation. In reality, many challenges confront the family that may lead to the deterioration or collapse of this vital institution. One of the essential pillars that enables a Muslim family to remain resilient in the face of both internal and external corruption is the implementation of the hisbah concept. Hisbah, as a religious duty to prevent wrongdoing (nahi munkar), is urgently needed to be revived as a living culture within the family. The purpose of this study is to explore how hisbah plays a role in strengthening Muslim families and preserving Islamic values within them. This paper employs a qualitative descriptive-analytical method based on library research, examining authoritative textual sources from Islamic scholars regarding hisbah and the family. The findings indicate at least five significant roles of hisbah that can be elaborated to reinforce the argument on the importance of implementing this concept within the family sphere. Keywords: Family, Hisbah, Nahi Munkar